2017
DOI: 10.4103/jcrt.jcrt_767_16
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hypofractionation (OCTA SHOT): Palliative radiation schedule in advanced head and neck carcinoma

Abstract: The study concludes that this "octa shot" is an effective palliative radiotherapy schedule. With a decreased duration of hospital stay, it is also favorable for outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…In India, there was almost a similar ORR along with significant symptom relief. 19 In contrast to our findings, research conducted in the Netherlands used 50 Gy in 16 fractions for SCC and 45% of patients achieved a CR. This could be because all patients had a considerably greater dosage of radiation with equivalent dose in 2 Gy fractions (EQD2) for tumors about 54.69 Gy 20 compared with our patient's maximal dose with a quad-shot regimen for nine patients, where the EQD2 is 50.69 Gy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In India, there was almost a similar ORR along with significant symptom relief. 19 In contrast to our findings, research conducted in the Netherlands used 50 Gy in 16 fractions for SCC and 45% of patients achieved a CR. This could be because all patients had a considerably greater dosage of radiation with equivalent dose in 2 Gy fractions (EQD2) for tumors about 54.69 Gy 20 compared with our patient's maximal dose with a quad-shot regimen for nine patients, where the EQD2 is 50.69 Gy.…”
Section: Discussioncontrasting
confidence: 99%
“… 18 In addition, other existing regimens, such as 28 Gy in eight fractions, are effective in symptom management. 19 The main difference between our study and other studies is that we included all histologic subtypes in which symptom improvement is found, whereas most other studies only addressed SCC.…”
Section: Discussionmentioning
confidence: 96%
“…Jakhar et al [14] Octa shot study, first response evaluation at 15 days after the day of treatment started, 3 months and 6 months respectively (p Value=0.0001). Grade 3 skin toxicity in 1 pt in Octa shot vs 0 in Quad shot.…”
Section: Resultsmentioning
confidence: 98%
“…Mudgal et al [20] observed good objective response in 82.6% and 84.7% of patients at primary and nodal sites, respectively. Jakhar et al [21] performed a pilot study to evaluate the effect of an accelerated hypofractionated 4 days schedule (octa shot) in providing palliation to such advanced cases of head and neck cancer. After completion of radiotherapy, first response evaluation done at 15th day showed ≥50% objective response in 14 patients.…”
Section: Discussionmentioning
confidence: 99%